2023
DOI: 10.1007/s00198-023-06807-6
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between type 2 diabetes mellitus and bone mineral density: a Mendelian randomization study in an East Asian population

Abstract: Summary It remains unclear whether the relationship between type 2 diabetes mellitus (T2DM) and bone mineral density (BMD) reflects causality in East Asian populations. Herein, a Mendelian randomization study conducted in East Asian population enhances the current clinical cognition that T2DM is not associated with reduction in BMD. Purpose A Mendelian randomization (MR) approach was utilized to investigate the relationship between type 2 diabetes mellitus (T2DM) and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 68 publications
0
2
1
Order By: Relevance
“…Previous studies have conducted Mendelian randomization (MR) studies in East Asian populations, which con rmed a causal relationship between type 2 diabetes and higher BMD, but no causal relationship with decreased BMD. However, these studies did not differentiate between different sites of BMD [5]. In contrast to the conclusion of another MR study, which suggested that type 2 diabetes is causally associated with femoral neck BMD but not with lumbar spine BMD, our results are inconsistent with this nding [6].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have conducted Mendelian randomization (MR) studies in East Asian populations, which con rmed a causal relationship between type 2 diabetes and higher BMD, but no causal relationship with decreased BMD. However, these studies did not differentiate between different sites of BMD [5]. In contrast to the conclusion of another MR study, which suggested that type 2 diabetes is causally associated with femoral neck BMD but not with lumbar spine BMD, our results are inconsistent with this nding [6].…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, a multivariable MR analysis was performed to assess the causal relationship between MDD and VTE, adjusting for education and BMI in our models to assess the effect of potential confounders. The multivariable MR simultaneously considers multiple exposure factors; it limits the corresponding effects of SNP exposure on the characteristics of other assumed risk factors and eliminates possible biases ( Huang G. et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…As genetic variants are assigned randomly at conception, MR circumvents confounding factors and reverse causality, common issues in traditional observational studies (13). Additionally, the precision of gene variant sequencing signi cantly reduces bias from measurement errors (14). This study employed two-sample MR analysis, utilizing the pooled statistics from genome-wide association studies (GWAS), to investigate the causal relationship between serum uric acid and cardiovascular disease (CVD), thereby contributing novel insights for CVD prevention.…”
Section: Introductionmentioning
confidence: 99%